Development of The Performance Assessment Based on Cassava Peel Waste Project to Measure Creative Thinking Skills of Junior High School Students - Chansyanah, Chansyanah; Fadiawati, Noor; Syamsuri, Muhammad Mahfudz Fauzi (Jurnal Pendidikan MIPA, 2021)
This study aims to develop a performance assessment based on the cassava peel waste processing project. This research uses methods of research and development 4D models which are only carried out until the stage of develop. At the define stage, a literature study and a preliminary study are carried out. At the design stage, planning and preparation of the initial draft are carried out in the form of performance assessments. In the develop stage, two science education experts validated the suitability of the content and construction of the performance assessment instrument to Torrance’s framework of indicators creative thinking skills. The product of the validation results was then responded to the suitability of the content and construction aspects of the indicators of creative thinking skills by three science teachers. The results of expert validation and teacher responses indicate that the performance assessment instrument product is very suitable to be used to assess student performance in integrated science learning based on cassava peel waste treatment projects.Keywords: performance assessment, cassava peel waste project, creative thinking skills. DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp305-311